Race against time to save human lives during the COVID-19 with vaccines: Global evidence - Phuc V. Nguyen; Toan L. D. Huynh; Vu M. Ngo; Huan H. Nguyen (Global Labor Organization (GLO), 2021)
Voluminous vaccine campaigns are used globally since the COVID-19 pandemic owes devastating mortality and destructively unprecedented consequences on different aspects of economies. Notwithstanding different approaches to measure the effectiveness of COVID-19 vaccines in clinical medicines, this paper sheds new light on the efficacy of COVID-19 vaccines by using the difference-in-differences (DiD) design of 127 countries in the daily frequency from February 2020 till the end of August 2021. We show that the number of new deaths per million significantly decreases after half of the population is vaccinated, but the number of new cases witnesses an insignificant change. We found that the effects are more pronounced in Europe and North America by offering insights about different continents. Our results remain robust after using other proxies and testing the sensitivity of the vaccinated proportion, providing causality and evidence that expanding and expediting COVID-19 vaccination can save human lives.
Keywords: I10; I18; 330; COVID-19; global scope; effectiveness; vaccines